Penerapan Model Pembelajaran Problem Solving Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Menyelesaikan Masalah Segi Empat dan Segitiga - Zebua, Nesti Surya Astuti (CARTESIUS : Jurnal Pendidikan Matematika, 2019)
This study aims to determine whether the application of the Problem Solving learning model can improve students' mathematical critical thinking skills. This type of research is Classroom Action Research (CAR). The subjects in this study were students of class VII SMP Yos Yoseph Medan, which consisted of 32 students. The object in this study is the Problem Solving learning model to improve students' critical thinking skills in solving mathematical problems. Based on the analysis of research data, the results obtained are: the initial test of mathematical critical thinking ability of students is still relatively low that is obtained a classical average of 49.84, as many as 8 students who completed 25% with a percentage of 25% while students who did not complete as many as 24 people with 75% percentage. The results of the first cycle test after using the Problem Solving learning model obtained a classical average value of 63.90, 17 students completed with a percentage of 53.12%, while students who did not complete as many as 15 people with a percentage of 46.87%. In the second cycle after making improvements to the learning model Problem Solving obtained an increase in the classical average value of 75.78 students who completed 26 students with a percentage of 81.25% while students who did not complete as many as 6 people with a percentage of 18.75%. So it can be concluded that the Problem Solving learning model that has been applied can improve students' mathematical critical thinking skills. This is supported by the data obtained by the average classical completeness of students' mathematical critical thinking skills obtained by the Problem Solving learning model in cycle II higher than cycle I.